2015
DOI: 10.1007/s00432-015-2080-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the clinical relevance of 17q25.3 copy number and three-dimensional telomere organization in non-small lung cancer patients

Abstract: The 3D telomere profiles may differentiate NSCLC patients with different histologies, EGFR, and smoking statuses, rendering them a potential biomarker for distinguishing these clinically relevant histological and molecular subtypes of lung cancer. Highly frequent clonal gain of cytoband 17q25.3 was also demonstrated, suggesting an important biological role for the genes in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Further, Sunpaweravong et al . 39 have implicated that gains of cytoband 17q25.3 are found in 61% lung cancer patients, underscoring a potential biological role for the genes within this region in the progression of lung cancer, which further substantiates the fact that there are many oncogenes located at chromosome 17. Significantly, loss of heterozygosity for the short arm of chromosome 17 has been demonstrated in a 4-year-old boy with GBM 40 .…”
Section: Discussionmentioning
confidence: 82%
“…Further, Sunpaweravong et al . 39 have implicated that gains of cytoband 17q25.3 are found in 61% lung cancer patients, underscoring a potential biological role for the genes within this region in the progression of lung cancer, which further substantiates the fact that there are many oncogenes located at chromosome 17. Significantly, loss of heterozygosity for the short arm of chromosome 17 has been demonstrated in a 4-year-old boy with GBM 40 .…”
Section: Discussionmentioning
confidence: 82%
“…Sunpaweravong et al reported that gains of chromosome 17 were observed in approximately one third (38.9%) of NSCLC patients while a majority (61%) harbored clonal gains of cytoband 17q25.3. These patients also had a tendency towards poorer survival outcome ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…c-Myc, as a transcription and replication factor, regulates multiple genes that control cell growth in varied cancer types including NSCLC. Copy number gains of cytoband 17q25.3, along with chromosome 17, have been reported in patients having NSCLC, emphasizing its clinical significance as a potential molecular target for therapy in this cancer ( 2 ). In pre-clinical studies, the upregulation of c-Myc has been found to lead to accelerated tumor development associated with duplication of the syntenic human cytoband 17q25.3, emphasizing the important role of this region in tumorigenesis ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…A common genetic feature of neuroblastoma and medulloblastoma is segmental gain of chromosome 17q, which in both diseases is a predictor of poor prognosis [ 8 , 45 , 52 ]. Frequent gain of chromosome 17q is also observed in cancers with epithelial, neural or hematopoietic origin [ 53 , 54 , 55 , 56 , 57 , 58 ]. This suggests that one or multiple genes important for tumorigenesis are located on 17q.…”
Section: Discussionmentioning
confidence: 99%